ACTIVITIES USED IN COMMUNICATIVE LANGUAGE TEACHING - Fadilah, Ridha (Khazanah: Jurnal Studi Islam dan Humaniora, 2009)
Communicative Language Teaching (CLT) is an approach to the teaching of second and foreign languages that stress on functional as well as structural aspects of language, combining these into a more fully communicative view. Learners learn the language used in real life by using target language in the classroom. It is appropriate to use communicative approach in teaching and learning language. It can make students able to communicate effectively in target language based on structural, functional and social meaning. In this paper, I will present communicative language teaching versus whole language teaching; structural, functional and social meaning of language; and classroom activities used in communicative language teaching.